Does Chapter 11 Save Economically Inefficient Firms? - Michelle J. White (Washington University Law Quarterly, 1994)
This Article presents a game theoretic model that explains why Type I error may occur in bankruptcy.
Keywords: Corporate finance; United States; Bankruptcy reorganization